Bio-social determinants of health-related quality of life of middle aged (45–59 years) population in India. Issue 1 (March 2020) - Nagarkar, Aarti; Kulkarni, Snehal; Gadkari, Rashmi
Purpose: Inadequate research on midlife health-related quality of life particularly in low-and-middle-income countries has often led to poor recognition of the issues in health programmes and policy. To address these concerns, this study was aimed at examining health-related quality of life and its determinants in middle-aged (45–59 years) men and women in low-resource settings in India. Methods: Data on health-related quality of life and other relevant parameters were collected from 1112 individuals between 45 and 59 years of age from an urban agglomeration of Pune, India. Independent t -test was used to determine the association between means of Short Form-12 and other variables. Multilinear regression analyses were conducted to study the direction of these associations. Results: The mean physical and mental component scores were 45.33 (±8.88) and 51.48 (±9.87), respectively. After adjusting for other variables, functional impairment emerged as a common factor that was negatively associated with physical and mental component scores of men (PCS: −5.557, 95%CI = −6.793 to −4.322; MCS:−1.816, 95% CI = −3.443 to −0.189) and women (PCS: −7.985, 95%CI = −9.782 to −6.188; MCS; = −2.289, 95% CI = −4.160–0.419). Good life satisfaction was positively associated with physical scores in men (2.300, 95%CI = 1.180 to 3.421) and mental scores in women (3.066, 95%CI = 1.333 to 4.798). Unemployment, sitting hours (>3) and no physical activity affected men, while lower education, marital status, body mass index and chronic illness affected health-related quality of life of women at midlife. Conclusions: Functional decline, level of life satisfaction and stress affected health-related quality of life of middle-aged individuals in India.